2003
DOI: 10.1007/s00056-003-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

Interocclusal Clearance during Speech and in Mandibular Rest Position

Abstract: This method can be used only in connection with mm. consonants. Speaking the word "Ohio" yielded excessively high values in all methods, so that this word has to be rejected as a speech sample. Cephalometric registration produced values with slight interindividual variations. In practice, however, this method is unsuitable for use with orthodontic patients because of the additional radiation exposure involved in producing an additional lateral cephalogram. For good reproducibility, practicing or frequent repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The belief that the closest speaking space is smaller than the FS was not supported by that study. More recently, Meier et al [19] concluded that none of the registration methods studied display clear-cut superiority to the others. Therefore, nonocclusal advantages, such as airway patency, may help the clinician decide on which registration protocol to follow.…”
Section: Discussionmentioning
confidence: 98%
“…The belief that the closest speaking space is smaller than the FS was not supported by that study. More recently, Meier et al [19] concluded that none of the registration methods studied display clear-cut superiority to the others. Therefore, nonocclusal advantages, such as airway patency, may help the clinician decide on which registration protocol to follow.…”
Section: Discussionmentioning
confidence: 98%
“…The precision of speech articulation is related to the freedom of the mandibular movements, modifying the spaces in order to allow the different articulatory positions of each sound (2). Furthermore, analysis of the mandibular movements during speech has been a useful method for determining the vertical dimension of dental occlusion, anterior guideline and tooth position in the rehabilitation treatment of patients (3). Mandibular movement dimensions are also important variables in the evaluation of speech patterns (4).…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular movement dimensions are also important variables in the evaluation of speech patterns (4). They are highly coordinated and do not involve dental contact (3).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Additional advantages of electronic axiography is avoidance of radiation exposure and real-time threedimensional representation of mandibular movements. 26 Most of the studies that observed TMJ anatomy and function used one specific sagittal condylar inclination angle 14,17,19,27,28 describing the left and right joints. Existing data about intraindividual variations of the sagittal condylar path are scarce.…”
Section: Introductionmentioning
confidence: 99%